Reszinate—A Phase 1/2 Randomized Clinical Trial of Zinc and Resveratrol Utilizing Home Patient-Obtained Nasal and Saliva Viral Sampling - Kaplan, Henry G.; Wang, Kai; Reeves, Kimberly M.; Scanlan, James M.; Nunn, Christopher C.; Kieper, Douglas A.; Mark, Joshua L.; Lee, Inyoul; Liu, Rachel; Jin, Ruyun; Bolton, Michael J.; Goldman, Jason D. (Frontiers in Drug Discovery, 2022)
Background: Safe, effective, inexpensive treatment for COVID-19 is an urgent unmet medical need. Zinc and resveratrol have been reported to have antiviral activity and resveratrol may increase zinc activity at the site of replication by increasing intracellular zinc concentrations. Methods A 1:1 randomized, placebo-controlled trial of zinc 150 mg plus resveratrol 4 grams daily for 5 days versus placebos in outpatients with SARS-CoV-2 was carried out 9/21/2020 – 1/22/2021 in Seattle, Washington. Viral shedding was followed with patient self-collected nasal and saliva samples by measuring qRT-PCR for SARS-CoV-2 N gene days 1-7,10,14. Patients filled out a web-based questionnaire on days 1-14 to report symptoms, vital signs and adherence to study intervention. Results 30 participants (14 treatment; 16 placebo) had ≥1 day of the protocol treatment and were evaluable for the primary or secondary outcome. There was no difference in viral shedding between groups. There was a non-statistically significant trend toward more rapid decrease in symptoms in the treatment group. Viral shedding was similar between patient self-collected mid-turbinate nasal swabs and expectorated saliva samples with good correlation. Conclusion SARS-CoV-2 shedding and COVID-19 symptoms were not statistically significantly decreased by treatment.. Viral shedding correlates well between patient-obtained home nasal swab and saliva sampling.